Especies y biotipos de moscas blancas (Homoptera: Aleyroridae) en cultivos semestrales de Colombia y Ecuador - Quintero, C.=700 1 Rendon, F.; Garcia, J.; Cardona, C.; Lopez Avila, A.; Hernandez, P.
(Es, En)
Ilus., 15 ref.
Keywords: BEMISIA TABACI; TRIALEUDORES VAPORARIORUM; RAPD; DISTRIBUCION GEOGRAFICA; ESPECIES; BIOTIPOS; COLOMBIA